High expression of ZFP36L2 correlates with the prognosis and immune infiltration in lower-grade glioma - Zhou, Min; Li, Jinquan; Chen, Cheng (Frontiers in Genetics, 2022)
Background: The ZFP36 Ring Finger Protein Like 2 (ZFP36L2) is an RNA-binding protein that regulates gene expression at post-transcriptional level. However, the clinical significance and prognostic value of ZFP36L2 in lower-grade glioma (LGG) remain unclear. Method: ZFP36L2 expression was investigated using public datasets and the prognostic merit of ZFP36L2 with LGG patients was further evaluated. The potential biological role of ZFP36L2 in LGG was identified by performing functional analyses. We also examined the correlation between ZFP36L2 expression and the immune infiltration. Finally, the predictive value of ZFP36L2 to immunotherapy was assessed. Result: ZFP36L2 was highly expressed in LGG patients and overexpressed ZFP36L2 predicted poor clinical outcomes. We further identified ZFP36L2 as an independent prognostic factor. The results of functional analysis indicated that ZFP36L2 was involved in multiple immune response-related pathways in LGG. Furthermore, high expression of ZFP36L2 was significantly and positively correlated with immune infiltration. Finally, we found that expression of ZFP36L2 positively correlated with the immune checkpoint PD-L1 and ZFP36L2 low expression cohort gained better benefit from immunotherapy. Conclusion: Our findings demonstrate that ZFP36L2 is a potential biomarker for LGG, highlighting its potential as a therapeutic target in immunotherapy.